THE CONTENT OF PEDALOGICAL EXPERIENCE TEST WORK - Sakhibova Ugiloy Nuraliyevna (International Scientific and Current Research Conferences, 2023)
This article describes the content of pedagogical experience test work and the most appropriate mental models of learners, from which it can be concluded that learners become rational while mastering the communicative competence of a foreign language based on rational methodology.